A case study on actual water pressure measurements at an open pit excavated in strong, tight rock and the implications for slope design - Rougier, M; Castro, LM; Birchall, D (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Precedent experience is that deep open pit slopes in strong, tight rock masses with high groundwater pressure will not exhibit rock mass failure. The phenomenon is not disputed. It is noted that simple limit equilibrium or finite element slope stability models, often relied upon in mine design and feasibility assessment, can indicate the contrary for high groundwater pressure conditions. In part this is because case history examples on actual groundwater pressure information from this type of open pit are limited. Consequently, over-conservative groundwater conditions can on occasion been assumed for stability analysis purposes. This paper presents a case study of the results of actual measurements of pore water pressure during pit development using vibrating wire piezometers. They were taken for the purpose of addressing risk management concerns over non-conservative stability analysis results for pit deepening and expansion of the Williams open pit at Barrick Gold's Hemlo Operations. The property is situated on the north shore of Lake Superior near Marathon, Ontario, Canada, in an area of moderate hydraulic recharge. The actual drawdown cone was found to be tight to the pit shell at depth, yet broader than expected near−surface. This may have been due to structural features and the interpreted effect of blast damage or the combination of slow excavation and moderate recharge. Site-specific observations are presented in terms of their implications for future slope design at Hemlo and in terms of the groundwater aspect of slope stability modelling in tight rock in general, particularly where limited information is available.